Bioremediation of phenol pollution - Abd. Shukor, Mohd. Yunus; Syed, Mohd Arif; Shamaan, Nor Aripin; Mat Arif, Noorliza; Ahmad, Siti Aqlima (2011)
The present invention relates to a bioremediation of phenol pollution in environment. Degradation of phenol is very important as it is highly toxic and carcinogenic. Newly isolated pure bacterial culture of Rhodococcus sp. strain AQ5NOL 2 with accession number KCTC 11961BP is contacted with phenol compound at optimum condition resulting in the conversion of the phenol compound to non-toxic products. The pure bacterial culture of Rhodococcus sp. strain AQ5NOL 2 is capable of degrading high amount of phenol up to 1500 mg/L.